2014
DOI: 10.22436/jmcs.012.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Application Of Reduced Differential Transformation Method For Solving Fourth-order Parabolic Partial Differential Equations

Abstract: The purpose of this paper is to obtain the approximate solution of fourth-order parabolic partial differential equations by the reduced differential transform method (RDTM).This method provides the solution in the form of a convergent series with easily calculable terms. Comparing RDTM with some other methods in the literature shows present approach is very simple, effective, powerful and can be easily applied to other linear or nonlinear PDEs in science and engineering.Keywords: Reduced differential transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…In this study, we successfully employed the FRDTM to find the approximate and exact solutions of three-dimensional fourth-order time-fractional parabolic partial differential equations with variable coefficients taking the fractional derivative in Caputo sense. It is found that the results we obtained in Examples 1 and 2 when α � 1 are in excellent agreement with the exact solutions obtained by VIM [35], ADM [36], and RDTM [37]. Also, the illustrated examples demonstrate that the suggested technique can be observed as a fast, simple, and efficient tool for computing three-dimensional fourth-order time-fractional parabolic partial differential equations (PDEs).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In this study, we successfully employed the FRDTM to find the approximate and exact solutions of three-dimensional fourth-order time-fractional parabolic partial differential equations with variable coefficients taking the fractional derivative in Caputo sense. It is found that the results we obtained in Examples 1 and 2 when α � 1 are in excellent agreement with the exact solutions obtained by VIM [35], ADM [36], and RDTM [37]. Also, the illustrated examples demonstrate that the suggested technique can be observed as a fast, simple, and efficient tool for computing three-dimensional fourth-order time-fractional parabolic partial differential equations (PDEs).…”
Section: Discussionsupporting
confidence: 76%
“…As it can be seen from these tables, when the value of the fractional order α becomes close to 1, the obtained FRDTM solutions of Examples 1 and 2 are close to the exact solutions of its respective classical (nonfractional) equations obtained by different methods. In particular, when α � 1, the FRDTM solutions of the mentioned examples are in excellent agreement with the exact solutions of their corresponding classical (nonfractional) form, for details, see [35][36][37].…”
Section: Numerical Results and Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Thirdly, this method can reduce the size of the calculations and can provide an analytic approximation, in many cases exact solutions, in rapidly convergent power series form with elegantly computed terms ( [37] and see the references therein). Moreover, the reduced differential transform method (RDTM) has an alternative approach of solving problems to overcome the demerit of discretization, linearization, or perturbations of well-known numerical and analytical methods such as Adomian decomposition, differential transform, homotopy perturbation, and variational iteration [37][38][39].…”
Section: Introductionmentioning
confidence: 99%